Journey : travel diary of a daydreamer - Billout, Guy. (Mankato, Minn. : Creative Education, 1993)
Illustrations without words depict scenes out of a train window as the train moves through the countryside--and through time.
K-3
K-3
School Library Journal
Publisher's Weekly
Horn Book
NP
Keywords: Stories without words; Railroad trains -- Fiction; Stories without words; Railroads -- Fiction